Questions about Roger Scruton (American Journal of Islam and Society, 2012)
Roger Scruton, known for his good-natured conservatism and general attemptsto defend traditional Western life, seems blind to the novelty ofour globalized world as he conflates Islam with radical Islam and attacksMuslims as though all were Islamists. Genial style notwithstanding,his indictment of Islam and Muslims is inaccurate and his desire todeny Muslims the right to live as Muslims in their own or Western politiesanything but good-natured. Alas, until Muslims become secular andagree to imbibe alcohol, Scruton will reject them as impossibly asocial.He ignores that there are many faces of Islam varying in place andtime as well as social milieu. That meshes with his devotion to viewingreligious conviction through the lenses of bourgeois Western mores andderiding piety. Though appealing to populist sentiment, it does not rise tothe standard of serious criticism or come near the scholarly obligation togive the arguments and the actions we oppose their strongest defense andthen probe for what is weak ...